Exploring electromyography for assistive technology: feasibility, usability and performance of a dry sensor EMG switch. - Judge, Simon (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: Switch access is a tool used by many individuals with physical disabilities. Switches used in assistive technology are typically electro-mechanical. Electromyography (EMG) has previously been suggested for assistive technology switch access but has been little explored. Materials and Methods: An exploratory study aiming to investigate the feasibility, usability and performance of a dry sensor EMG switch when used by individuals with physical disabilities to control assistive technology was conducted. Results: Twelve participants with a range of underlying conditions trialled a novel dry sensor EMG switch. Switch reaction performance data for both EMG and conventional switches and qualitative feedback from semi-structured interviews were collected and tabulated. Results showed that the EMG switch was feasible to use in a range of placements and with a range of individuals, that it was feasible in some situations where a conventional switch was not, and that it may be more appropriate for those with hypokinetic movement disorders. Some participants described use of the EMG switch as less effortful and fatiguing. Some participants had faster reaction times using the EMG switch compared to conventional switches, the fastest average reaction time reported in the study (483 ms) was using the EMG switch. More false positive activations occurred when using the EMG switch and participants described this as impacting on usability. Setup complexity was also noted as a key usability barrier. Conclusions: This study highlights potential benefits of EMG switches but suggests further development is needed to improve ease of use and minimise false activations if EMG switches are to achieve broader adoption. IMPLICATIONS FOR REHABILITATION: EMG switches, using EPS dry sensor technology, may currently be appropriate as a switch access method for those with physical disabilities. It is likely that EMG switches may be more appropriate for those with hypokinetic movement disorders such as MND and DMD. It is likely that EMG switches may be more appropriate for those where no other switch access method can be found. EMG switches may offer some performance advantage in quicker reaction times which may provide benefit for some individuals, however EMG switches using current technologies may also result in users experiencing an increased rate of false positive activations.